Decoding the Symphony of Satisfaction, Commitment and Trust as Predictors of Customer Loyalty in Demarketing Situations - Kigen, Fiona; de Villiers, Marike Venter (International Review of Management and Marketing, 2024)
In the realm of demarketing within the banking industry, banks often need to reject customers for certain products while maintaining overall relationships. Understanding the interplay of satisfaction, trust, and commitment is crucial in this delicate dance. This study, grounded in the commitment-trust theory of relationship marketing, investigates how these factors predict customer loyalty in demarketing situations. Using a quantitative approach with an experimental design, the study employed a vignette followed by a survey to gather data. A total of 505 responses were analyzed through Structural Equation Modelling. The findings indicate support for four hypotheses while two were rejected. Satisfaction had a positive but weak and marginally significant effect on commitment and a very strong, highly significant positive effect on trust. Conversely, satisfaction had no significant direct effect on loyalty. Trust demonstrated a significant positive effect on commitment but no direct impact on loyalty. Commitment, however, showed a very strong and highly significant positive effect on loyalty. Commitment and trust also played key roles as mediators in the relationship between satisfaction and loyalty. The study provides valuable insights for firms navigating demarketing scenarios, aiming to foster stronger and more enduring customer relationships.